2022
DOI: 10.1186/s12943-022-01640-7
|View full text |Cite
|
Sign up to set email alerts
|

PDGFRβ promotes oncogenic progression via STAT3/STAT5 hyperactivation in anaplastic large cell lymphoma

Abstract: Background Anaplastic large cell lymphoma (ALCL) is an aggressive non-Hodgkin T cell lymphoma commonly driven by NPM-ALK. AP-1 transcription factors, cJUN and JUNb, act as downstream effectors of NPM-ALK and transcriptionally regulate PDGFRβ. Blocking PDGFRβ kinase activity with imatinib effectively reduces tumor burden and prolongs survival, although the downstream molecular mechanisms remain elusive. Methods and results In a transgenic mouse mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…In addition to the classical and simple signal transduction of the receptor-JAK-STAT- downstream pathway, the activation of some receptor tyrosine kinases (RTKs) can phosphorylate STAT through Src kinase, including epidermal growth factor receptor (EGFR) and platelet-derived growth factor receptor (PDGFR). 61 , 62 It can also activate mitogen-activated protein kinase (MAPK) through activation of the RTK/Ras pathway. MAPK can specifically phosphorylate the serine site (Ser727) at the C-terminus of STAT to enhance the transcriptional activity of STAT.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the classical and simple signal transduction of the receptor-JAK-STAT- downstream pathway, the activation of some receptor tyrosine kinases (RTKs) can phosphorylate STAT through Src kinase, including epidermal growth factor receptor (EGFR) and platelet-derived growth factor receptor (PDGFR). 61 , 62 It can also activate mitogen-activated protein kinase (MAPK) through activation of the RTK/Ras pathway. MAPK can specifically phosphorylate the serine site (Ser727) at the C-terminus of STAT to enhance the transcriptional activity of STAT.…”
Section: Discussionmentioning
confidence: 99%
“…Lineage transition from Adeno to NEPC is relatively a common type of cancer cell plasticity in ADT-treated PCa [ 9 ]. It has been reported that STAT5A has a tightly correlation with lineage plasticity both in stem cells [ 56 ] and in tumors [ 57 , 58 ]. Therefore, we wondered whether PAX6 could promote NE trans-differentiation via STAT5A mediated changes of cells lineage plasticity.…”
Section: Resultsmentioning
confidence: 99%
“…This is supported by the fact that activating STAT5B mutations and particularly STAT5B N642H also occur in T cell large granular lymphocytic leukemia, T cell prolymphocytic leukemia, and various γδ T cell–derived leukemias/lymphomas ( 18 ). Furthermore, STAT5 activation is targetable in cutaneous T cell lymphomas, bearing STAT5A and STAT5B copy number gains, and PDGFRβ-driven anaplastic large cell lymphoma ( 55 , 60 ). STAT5 activating kinase triggers might lead to similar molecular consequences as STAT5B N642H , highlighting broad applicability of our results.…”
Section: Discussionmentioning
confidence: 99%